(untitled) (GENDER EQUALITY: International Journal of Child and Gender Studies, 2018)
This study explored qualitatively pictures of students experiences in developing extra activities regarding the talents and skills development. By implementing the qualitative design and interviews, the selected female studens were questioned to share their experiences.The research participants were mixed alumni and current English Department students of Universitas Islam Negery Ar-Raniry Banda Aceh. The sampling technique was purposive. The conclusion shows that most students expressed ther great thought on benefits of participating in extracurricular and talent competition activities for most of the reasons. Indeed, the attaining of competition is greater opportunities among female students in skills and experiences.